2015
DOI: 10.1111/apm.12383
|View full text |Cite
|
Sign up to set email alerts
|

Microbes of the tonsils in PFAPA (Periodic Fever, Aphtous stomatitis, Pharyngitis and Adenitis) syndrome - a possible trigger of febrile episodes

Abstract: Periodic Fever, Aphtous stomatitis, Pharyngitis, and Adenitis (PFAPA) is a childhood febrile syndrome that is often cured by tonsillectomy (TE). We hypothesized that microbes present in the tonsils may act as a trigger for the activation of inflammasomes and investigated the microbiology of the tonsils in PFAPA patients and controls. We recruited 31 consecutive children who underwent TE due to PFAPA; 24 children who underwent TE due to other reasons served as controls. We cultured all the samples for bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Since the signs of inflammation in PFAPA often localise in the pharyngotonsillar region, and tonsillectomy has been shown to be an effective treatment for the syndrome , the palatine tonsils have been a logical focus of research. The histology of palatine tonsils in PFAPA has not shown significant differences when compared to tonsil tissues removed for other reasons , but the distribution of both B‐ and T‐lymphocytes and the production of pro‐ and anti‐inflammatory cytokines seem to be different . Tonsils removed from PFAPA patients have revealed smaller amounts of B‐lymphocytes and more naive polyclonal T‐lymphocytes when compared to tonsils removed for other reasons .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Since the signs of inflammation in PFAPA often localise in the pharyngotonsillar region, and tonsillectomy has been shown to be an effective treatment for the syndrome , the palatine tonsils have been a logical focus of research. The histology of palatine tonsils in PFAPA has not shown significant differences when compared to tonsil tissues removed for other reasons , but the distribution of both B‐ and T‐lymphocytes and the production of pro‐ and anti‐inflammatory cytokines seem to be different . Tonsils removed from PFAPA patients have revealed smaller amounts of B‐lymphocytes and more naive polyclonal T‐lymphocytes when compared to tonsils removed for other reasons .…”
Section: Resultsmentioning
confidence: 90%
“…With routine clinical microbiology, the throat or tonsillar samples of PFAPA patients have revealed no evident viruses or bacteria responsible for the symptoms . However, unspecific biofilms and Candida albicans were found more often and Staphylococcus aureus less often in tonsil samples removed from PFAPA patients compared to controls .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Cloacibacterium was isolated only from PFAPA patients' tonsils (6,7). The results suggest that microbial activity, together with exposure to various triggers, such as maternal smoking, with known immunomodulatory effects may lead to the development of PFAPA syndrome.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies support the hypothesis that PFAPA syndrome involves inflammasome-driven proinflammatory interleukin (IL)-1β production during febrile episodes (4,5). Inflammasomes may be activated by microbes or other environmental stimuli (6,7). Recent studies showed clear family clustering of PFAPA syndrome (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%